2019
DOI: 10.20944/preprints201901.0155.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic Significance of EIF4G1 in Patients with Pancreatic Ductal Adenocarcinoma<strong> </strong>

Abstract: Background: The advances of genomics have greatly improved the survival rate cancer patients. However, due to genetic heterogeneity, pancreatic ductal adenocarcinoma (PDAC) is still difficult to diagnose early and the survival rate is extremely low. Therefore, we identified biomarkers that predict the prognosis of PDAC patients by using independent cohort data. Methods: To develop a novel prognostic biomarker, we used gene expression and clinical data from The Cancer Genome Atlas (TCGA) and Gene Expression Omn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We used the following methods: Kaplan‐Meier survival curves with log‐rank test, Uno's C ‐index in the time‐dependent area under the curve (AUC) analysis, and AUC values in receiver operating characteristics (ROC) at 3 years to evaluate the accuracy of the risk stratification. These methods were performed in accordance with previously published studies . Values were obtained using the R packages “survival” and “survAUC.” In the Kaplan‐Meier analyses, we determined the optimal cutoff expression value of FAM213A that had the maximal Uno's C ‐index by fivefold cross‐validation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the following methods: Kaplan‐Meier survival curves with log‐rank test, Uno's C ‐index in the time‐dependent area under the curve (AUC) analysis, and AUC values in receiver operating characteristics (ROC) at 3 years to evaluate the accuracy of the risk stratification. These methods were performed in accordance with previously published studies . Values were obtained using the R packages “survival” and “survAUC.” In the Kaplan‐Meier analyses, we determined the optimal cutoff expression value of FAM213A that had the maximal Uno's C ‐index by fivefold cross‐validation.…”
Section: Methodsmentioning
confidence: 99%
“…These methods were performed in accordance with previously published studies. [16][17][18][19] Values were obtained using the R packages "survival" and "survAUC." In the Kaplan-Meier analyses, we determined the optimal cutoff expression value of FAM213A that had the maximal Uno's C-index by fivefold cross-validation.…”
Section: Survival Analysesmentioning
confidence: 99%
“…The formation and development of tumours are complex processes involving multiple factors, such as some key oncogenes and tumour suppressor factors 31 . In addition to promoting protein translation, EIF4G1 plays an important role in the initial stage of eukaryotic cell translation and is closely related to the occurrence and development of tumours 32,33 . Some studies have shown that the eukaryotic translation initiation factor EIF4G1 plays a positive role in the processes of tumour formation, proliferation and metastasis 19‐24 .…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition to promoting protein translation, EIF4G1 plays an important role in the initial stage of eukaryotic cell translation and is closely related to the occurrence and development of tumours. 32,33 Some studies have shown that the eukaryotic translation initiation factor EIF4G1 plays a positive role in the processes of tumour formation, proliferation and metastasis. [19][20][21][22][23][24] In the present study, we found that the mRNA and protein expression levels of EIF4G1 were upregulated in NSCLC tissues, as determined by RT-PCR and immunohistochemistry analysis, and the expression levels of EIF4G1 were closely related to the differentiation of tumour cells; the higher the expression of EIF4G1 was, the poorer differentiated the tumour was.…”
Section: Eif4g1 Regulates the Activities Of The Mtor Signalling Pathwaymentioning
confidence: 99%
“…This result is consistent with a previous study showing that serum histamine level is significantly lower in a murine allergic Rhinitis model after kaempferol administration. 23 High concentration of omega-6 administration can cause imbalance of omega-6 and omega-3 ratio. This can have negative effects on the health of mammalians.…”
Section: Discussionmentioning
confidence: 99%